Essential Oil Extraction(Aetheric Oil) Sweet Orange Skin (Citrus x sinensis) Using N-Hexane Solventand Ethyl Acetate - Ridwan, Magfira; Nuryanti, Siti; Afadil, Afadil; Diah, Anang Wahid M; Jura, Minarni Rama (Media Eksakta, 2025)
The purpose of this study was to determine the yield of squeezed orange peel essential oil extracted using n-hexane and ethyl acetate solvents and to determine the type of solvent that was good for the quality of squeezed sweet orange peel essential oil. The quality of the oil in terms of organoleptic, refractive index, specific gravity of essential oil, and solubility in 90% alcohol. Determination of the quality of essential oils is based on quality test results adjusted to SNI. The results showed that the yield of extracted sweet orange peel essential oil in each ratio (1:5, 1:3) using n-hexane and ethyl acetate were 0.100%, 0.096% and 0.067%, 0.043%. The results of the essential oil quality test from the two solvents (n-hexane and ethyl acetate) in each ratio (1:5, 1:3) were; Organoleptic tests showed different colors and aromas at n-hexane 1:5, which was golden yellow and had an orange flavor, 1:3, which was pale yellow and had a characteristic limonene aroma (orange aroma), while 1:5 ethyl acetate, which was brownish yellow and had a solvent aroma. , 1:3 which is brown and smells of solvent, refractive index test (1.472, 1.473 and 1.471, 1.471), specific gravity of oil (0.864 and 0.782), solubility in alcohol 90% at n-hexane 1:5 and 1:3 the same result was obtained, namely 1:8 clear, while ethyl acetate also obtained the same result, namely 1:13 clear. Based on these results, it shows that the highest yield was obtained from n-hexane solvent at a ratio of 1:5. However, to determine the quality of essential oils the best solvent was obtained from n-hexane at a ratio of 1:3.